Stakeholder Approach To Corporate Social Responsibility: Recipe For Sustainable Peace In The Niger Delta Region? - Lugard, Sunday Bontur (Journal of Sustainable Development Law and Policy, 2025)
Corporate Social Responsibility (CSR) is a pathway to positive and sustainable engagement of business-stakeholders in general and its host community in particular, especially when the operations of such enterprise have a way of negatively impacting the environment or other interests of such a community. Empirical research has shown that such engagement has a way of not just improving corporate-community relations but acts as a strategic roadmap to allow stakeholders take ownership of and buy in into corporate sustainability plans. This is one area International Oil Companies (IOCs) operating in Nigeria’s Niger Delta region have arguably floundered, and hence the ensuing and seemingly intractable confrontations from the host communities and militant groups who perennially feel left out of topdown CSR initiatives. This paper discusses the concept of “emotional equity” as a missing piece in community involvement in corporate sustainability in Nigeria. It examines how a stakeholder approach to CSR could serve as a participatory and level playing approach that would engender peaceful, symbiotic engagement and cohabitation between the IOCs and their host communities.